1995
DOI: 10.1007/bf00448953
|View full text |Cite
|
Sign up to set email alerts
|

Massive intercalary bone allografts in the treatment of primary and secondary bone tumors

Abstract: From 1981 to 1993, 21 patients received intercalary bone allografts for reconstruction of the extremity after en bloc tumor resection (15 malignant and 6 benign tumors). The allografts were collected from multiorgan donors and cryopreserved at -70 degrees C. The mean follow-up was 4.4 (range 1-13) years. The fate of the grafts was followed by conventional radiography, bone scintigraphy, and functional assessment. The overall survival rate of the 7 patients with high-grade malignancies was 86%. Solid union of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
2
11
0
3
Order By: Relevance
“…Our patients underwent osteosynthesis or implant surgery, and from bone scintigraphy studies, it is well known that bisphosphonates accumulate at sites of surgery and osteosynthesis. (6) Thus, in theory, our patients were facing a situation similar to the one reported by Amanat et al, with potential accumulation of drug in the fracture callus and at sites of osseointegration. However, further analysis by 2-wk intervals showed that total hip BMD at 12 mo was significantly increased in all patients dosed after 2 wk.…”
Section: Discussionsupporting
confidence: 61%
“…Our patients underwent osteosynthesis or implant surgery, and from bone scintigraphy studies, it is well known that bisphosphonates accumulate at sites of surgery and osteosynthesis. (6) Thus, in theory, our patients were facing a situation similar to the one reported by Amanat et al, with potential accumulation of drug in the fracture callus and at sites of osseointegration. However, further analysis by 2-wk intervals showed that total hip BMD at 12 mo was significantly increased in all patients dosed after 2 wk.…”
Section: Discussionsupporting
confidence: 61%
“…While the reports on the use of prosthetic diaphyseal replacements are few (Abudu et al 1996, Damron et al 1996, the outcome is favorable like that reported from the more extensive experience with allografts (Mankin et al 1987, Kattapuram et al 1989, Muscolo et al 1992, Donati et al 1993, Cara et al 1994, Voggenreiter et al 1995. Our results, which represent the longest follow-up to date, show promising longevity and function after prosthetic reconstruction of diaphyseal defects.…”
Section: Discussionsupporting
confidence: 60%
“…Implants must address the two major noninfectious complications of allograft reconstructions: nonunion and fracture. Reported healing rates vary from 70% to 89%, and the rate of long-term allograft fracture approaches 8% to 20% [1,7,18,19,30,31,33,34]. The two primary methods of fixation, plates and intramedullary devices, have unique benefits and weaknesses; however, no difference in healing rates has been elucidated [2,21,30].…”
Section: Discussionmentioning
confidence: 98%